Pelatihan Keterampilan Pembuatan Kreasi Buket sebagai Upaya Menumbuhkan Jiwa Kewirausahaan Ibu-Ibu PKK Desa Kebojongan - Rahayu, Sang Ayu Putu; Zaqiyaturrohmaniah, Alfi; Amelia, Siska; Sari, Dewi Ratna; Lestari, Fauziah Ayu (Universitas Negeri Semarang, 2023)
The bouquet creation training aims as an effort to improve and hone the skills of the villagers. This bouquet creation training is expected to foster an entrepreneurial spirit and increase MSMEs which boosts the economy of the Kebojongan Village residents. The implementation of the bouquet creation activity consisted of several stages: the preparation of tools and materials, the planning and trial stages, the socialization and discussion stages, and the practice and demonstration stages. The training participants had high enthusiasm and positively influenced the community's ability to make crafts from snack bouquets. Bouquet training, appropriately used and skillfully, can add to daily income.